Young people, social media, social network sites and sexual health communication in Australia: ‘this is funny, you should watch it - Evers, Clifton Westly; Albury, Kath; Byron, Paul; Crawford, Kate (University of Southern California, Annenberg School of Communication and Journalism, 2013)
Social media and social network sites (SNS) are an evolving area for sexual health communication with young people. They present opportunities and challenges for sexual health professionals and young people alike, such as learning through interactivity and addressing concerns about privacy. In this article, we present and discuss the findings from six rural and urban focus groups with young people in Australia about the use of social media and SNS for sexual health communication. We discuss a number of issues related to the use of social media and SNS for sexual health communication, such as concerns about bullying, privacy, and the stigma attached to sexual health.